Verification of Gamma Knife Output Dose Conformity with Treatment Planning System in Terms of Red, Green, and Blue Channels - Wijaya, Tabitha Ivana; Irhas, Irhas; Soediatmoko, Elia; Manik, Josua Timotius (Journal of Physics and Its Applications, 2024)
The calibration method using Gafchromic EBT-3 film is employed to verify the conformity of the Gamma Knife output dose compared to the Treatment Planning System (TPS). The films undergo exposure to doses of 5, 10, 15, 20, and 25 Gy on a phantom, followed by data processing and analysis using ImageJ, MatLab, and Microsoft Excel software. Assessment of the red, green, and blue channels is carried out to evaluate their sensitivity and conformity with the TPS doses. The film calibration curve shows that the red channel has the highest sensitivity among the other two channels, as indicated by the corresponding increase between dose and net Optical Density (OD). Calculation of the gamma index using Dose Difference (DD) and Distance to Agreement (DTA) values at 3% and 2.4 mm were used to determine the conformity of the film dose with TPS using the Gamma Passing Rate (GPR). The red, green, and blue channels obtained GPR values of 98.96%, 98.61%, and 98.27%, respectively. This result validates that the red channel achieved the highest percentage of conformity between film and TPS doses. However, the GPR values of the three channels have no significant difference. It is concluded that the red, green, and blue channels have a high percentage of conformity between the film dose and the TPS dose.